ANALISIS STABILITAS BETON ASPAL AC-BC DIDASARKAN DARI VARIASI SUHU PENCAMPURAN PADA KONDISI SUHU PEMADATAN MINIMUM DENGAN BAHAN PENGIKAT ASPAL RETONA BLEND 55 - Nurlely Nurlely; Fitrika Mita Suryani; Yuseva Yuseva (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2013)
Implementation of Asphalt Concrete work , in addition to the material that should be qualified , temperature is also a very important thing , either mixing temperature and compaction temperatures . According to Anonymous (1989 : 14 ) , the solidification temperature ranged between 90oC to 110oC , while the mixing temperature is 1600C . In this study analyzed against ter - mix asphalt concrete with a characteristic temperature variation does mixing of 1500C ; 1600C ; 1700C and 1800C , where the temperature compaction performed at 900C minimum compaction conditions . The purpose of this study is to look at the value of stability and other parameters on the value of the temperature variation with temperature of the mixture using a minimum compaction of asphalt material Retona Blend 55 so that the resulting parameters meet the requirements . This study begins with an examination of the material that covers the aggregate , asphalt and gradation Retona Blend 55 . Furthermore, the specimen was made by 15 specimen with 5 variations bitumen content of 4.5 % , 5 % , 5.5 % , 6 % , and 6.5 % made 3 pieces of samples for each bitumen content . OBC value obtained was 5.3 %. Based on the OBC Marshall test again with a mixture of temperature variations in a total of 12 test specimens . Marshall stability values obtained showed a decrease of requirements ( 1000 kg ) . the mixing temperature 150oC , 160oC , 170oC , and 180oC and at a temperature of 90oC solidification sequence is 454.77 kg ( 54.52 % ) , 502.92 kg ( 49.71 % ) , 598.53 kg ( 40.15 % ) , and 586.44 kg ( 41.36 % ) . The highest Marshall stability value of 598.53 kg obtained at mixing temperature of 170oC , but can not achieve the required stability which is 1000 kg . The results showed that the stability of the compaction temperature on the minimum condition can not be used to Laston AC - BC